Using Concept Mapping to Build Concept the Competence of School Principals - Mustamin Mustamin; M. Al Muzammil bin Hj. Mohd Yasin (Journal of Education and Learning (EduLearn), 2012)
More and more the competence concept of school principals have an impact on two conditions, namely: (1) to develop the concept can complement and support each other; and (2) to develop the concept of possible contradict, giving rise to different interpretations. Therefore, this becomes the main issue researchers to identify the competence concept of school principals with adaptation of Jackson-Trochim method that is capable of illustrating the concept of competencies. Results of adaptation Jackson-Trochim method that school principals should have three types of competencies to lead the school effectively and efficiently. Kind of competencies are such as school leadership, instructional leadership, and operational leadership. Based on these results, the adaptationof Jackson-Trochim method to build the competence concept of school principals suggests this concept obtained may serve as a reference for school principals continue to build competencies in the future